Designers' guide to EN 1991-1-4 : Eurocode 1: actions on structures, general actions. Part 1-4, - Cook, N. J. (Designers' guides to the eurocodes., 2007)
This text aims to provide the user with a commentary on the interpretation and use of EN1991, Eurocode 1: Actions on structures - General actions - Part 1-4: Wind actions. This title also includes a commentary on the changes introduced in the UK National Annex.